„Job satisfaction analysis of female Employees of IT Sector working from home during the pandemic of COVID-19 using interaction effect‟ - Shaikh, Dr. Naim; Pawar, Kishor; Kasat, Dr. Kishori; Deshpande, Dr. Abhijit (The journal of contemporary issues in business and government, 2021)
Since the pandemic of Covid-19, working from home has become a new normal. A relative psychological feeling and understanding of an individual is job satisfaction. It varies depending on various factors that influence or contribute, such as physical, financial, technological, social, and psychological factors. The main goal of the research is to understand the difference in job satisfaction of urban working women from the IT sector in India in a pandemic situation based on two factors namely marital status and nature of family. The study was confined to the urban working women in the IT sector in the city of Pune, India. This paper aims to study the impact of marital status and nature of family as a combined effect on the job satisfaction of female employees in the IT sector working from home during the pandemic situation of covid-19. A questionnaire gathered primary data and the respondents were female IT sector employees in Pune. In this background the present study was undertaken to analyse job satisfaction of working women in the IT sector during a pandemic situation. The sample consists of 238 career women working in the IT Sector of Pune, India. The questionnaire was Circulated online through Google Form to 300 respondents and received 238 responses from them. The received data tested for data fitment and further interaction effect was found. The interaction effect results show that marital status and nature of family are significantly associated with job satisfaction of female working employees of the IT sector. It opens for a thought to start rethinking women employee job satisfaction in terms of formulating employee support programs to maintain their level of job satisfaction to enhance productivity.